UJI TOKSISITAS DAN PENENTUAN AKTIVITAS ANTIOKSIDAN DENGAN METODE DPPH DARI METABOLIT SEKUNDER FRAKSI n-HEKSAN, ETIL ASETAT DAN METANOL-AIR DAUN SISIK NAGA (Drymoglossum piloselloides [Linn.] Pr.) - Erwin -; Dwi Fitria Sari; Chairul Saleh (PROSIDING SEMINAR KIMIA, 2013)
Phytochemical, toxicity test had been done that used Brine shrimp (Brine shrimp lethality test) and antioxidant activity test using methanol extract from sisik naga leaf (Drymoglossum piloselloides (Linn). Pr) fraction that taken from Kutai Kartanegara, East Kalimantan. Sisik naga leaf was extracted by methanol and then concentrated using rotary evaporator. Then that crude extract was fractioned by n-hexane, ethyl acetate and methanol-water. Based on phytochemical test of the sisik naga leaf show that crude methanol extract, n-hexane fraction and ethyl acetate fraction was contain alkaloid, flavonoid and steroid at methanol-water fraction was contain alkaloid and phenol. Brine shrimp lethality test show that lethality level of Artemia Salina (L) that used Probit SAS Analyze to determine value of Lethal Concentration 50% (LC 50 ). The test showed that the most active was crude n-Hexane extract with LC 50 value of 0,0910 ppm. Antioxidant activity test of extracts from crudge methanol and some variations fractioned using DPPH radical reduction (2,2 '-diphenyl-1-picrylhydrazil) using Spectrophotometer. The test showed that the most active and recommended to used as antioxidant is methanol-water fraction with IC 50 values is at 74.51 ppm and LC 50 values is at 87749.9219 ppm.